1978
DOI: 10.5271/sjweh.2703
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in the work atmosphere. II. Determination in a coke plant.

Abstract: The content of polycyclic aromatic hydrocarbons (PAH) in the work atmosphere of a coke plant was investigated on two occasions. Stationary, mobile, and personal sampling were used, and the samples were analyzed by glass capillary gas chromatography. Up to 39 PAH and heterocyclic compounds were identified in the samples. By personal sampling, the occupational exposure to PAH was determined to vary between 5 and 1,000 mg/m 3 . A study of the occurrence of PAH on particulate matter revealed that 98 % of the PAH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 7 publications
(10 reference statements)
4
32
1
Order By: Relevance
“…Polycyclic aromatic hydrocarbons (PAHs) are environmentally significant due to their widespread occurrence and potentially toxic to wildlife and humans (Bjøseth et al, 1978;Lioy and Daisey, 1986;Petry et al, 1996;Cousins and Jones, 1998;Weinstein et al, 2010). They mainly originate from anthropogenic activities, such as incomplete combustion of organic materials (e.g., wood, coal oil, gas, tobacco and straw), as well as from automobile exhausts and industrial processes (Yunker et al, 2002a(Yunker et al, , 2002b.…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are environmentally significant due to their widespread occurrence and potentially toxic to wildlife and humans (Bjøseth et al, 1978;Lioy and Daisey, 1986;Petry et al, 1996;Cousins and Jones, 1998;Weinstein et al, 2010). They mainly originate from anthropogenic activities, such as incomplete combustion of organic materials (e.g., wood, coal oil, gas, tobacco and straw), as well as from automobile exhausts and industrial processes (Yunker et al, 2002a(Yunker et al, , 2002b.…”
Section: Introductionmentioning
confidence: 99%
“…The National Institute for Occupational Safety and Health (NIOSH) (21) considers more than 500 ppm of naphthalene in air to be immediately dangerous to life or health. Bjeirseth et a1 (22) have reported vapor levels of 1.1 to 11 pg/m3 in a coke plant. Higher levels would be anticipated in naphthalene-producing industries and naphthalene-using industries such as wood preserving, coal-tar production, and the production of dyes, inks and similar compounds (1 3).…”
Section: T T H I S S T U D Y S H O W S T H a T O P E R A T O R S Inmentioning
confidence: 99%
“…Such workers are under an increased risk of cancer of the lungs and respiratory tract, and also of the urinary bladder (3,4,5,12). A recent study showed that coke plant workers were exposed to P AH concentrations of between 5 and 1,000 {lg/m 3 , and up to 39 different PAH and heterocyclic compounds were identified (2). Smokers, who are exposed to much lower concentrations of P AH, are also known to have elevated risks of bladder cancer (13).…”
Section: Introductionmentioning
confidence: 99%